2016
DOI: 10.1177/0004563216642255
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine replacement: a clinical endocrinologist’s viewpoint

Abstract: Despite the availability of thyroid hormone replacement for more than a century, there are still substantial challenges in practice and opportunities to improve treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 121 publications
(207 reference statements)
3
32
0
3
Order By: Relevance
“…Among the patients ( n = 116) submitted to the outpatient clinic due to persistent symptoms, 43% did not start combination therapy due to being overtreated with a S-TSH less than 0.1 mU/L or undertreated with a S-TSH of 4-56 mU/L -this is in accordance with Eligar et al [18] , underlining the importance of careful follow-up and adjustment of medication in this patient group.…”
Section: Discussionsupporting
confidence: 82%
“…Among the patients ( n = 116) submitted to the outpatient clinic due to persistent symptoms, 43% did not start combination therapy due to being overtreated with a S-TSH less than 0.1 mU/L or undertreated with a S-TSH of 4-56 mU/L -this is in accordance with Eligar et al [18] , underlining the importance of careful follow-up and adjustment of medication in this patient group.…”
Section: Discussionsupporting
confidence: 82%
“…In 2008, the Endocrine Society has published a position statement on this issue to ensure pharmacologic homeostasis of patients (https://www.endocrine.org/advocacy/priorities-andpositions/bioequivalence-of-sodium-levothyroxine). There is, however, general consensus that switching between different tablet T4 preparation should be avoided (2,9).…”
Section: How the Pharmaceutical Forms Of Oral Thyroxine Are Preparedmentioning
confidence: 99%
“…However, the number of interfering issues rendered often inadequate for a patient a dose that is satisfactory for another (8). It has been reported that 20% to 50% of patients fail to show a complete chemical and/or clinical response to a reference dose of thyroxine (9). The consequence of that is the need for an increased dose, care and monitoring (10).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with this disease are commonly managed through supplementation with synthetic thyroid hormone, with the aim of alleviating symptoms and restoring normal thyroid-stimulating hormone levels [7] Levothyroxine, the treatment of choice, is inexpensive, easy to administer and in most cases restores well-being while normalizing thyroid function. However, 30-50% of individuals on levothyroxine are either over-treated or undertreated, and others remain dissatisfied with treatment despite achieving thyroid hormone concentrations within the laboratory reference interval [8]. Treatment with constitutional homoeopathic medicine alone or along with levothyroxine leads to the cure of hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%